Peer Effects in Program Participation - Dahl, Gordon B.; Løken, Katrine V.; Mogstad, Magne (American Economic Review, 2014)
The influence of peers could play an important role in the take up of social programs. However, estimating peer effects has proven challenging given the problems of reflection, correlated unobservables, and endogenous group membership. We overcome these identification issues in the context of paid paternity leave in Norway using a regression discontinuity design. We find strong evidence for substantial peer effects of program participation in both workplace and family networks. Coworkers and brothers are 11 and 15 percentage points, respectively, more likely to take paternity leave if their peer was exogenously induced to take up leave. The most likely mechanism is information transmission about the costs and benefits of taking paternity leave, including increased knowledge of how an employer will react. The estimated peer effect snowballs over time, as the first peer interacts with a second peer, the second peer interacts with a third peer, and so on. This leads to long-run participation rates which are substantially higher than would otherwise be expected.